ARTIFICIAL INTELLIGENCE (AI) AND CYBERSECURITY LAW: LEGAL ISSUES IN AI-DRIVEN CYBER DEFENSE AND OFFENSE - Jaiswal, Amit; Mishra, Prakash Chandra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the legal and regulatory challenges posed by AI’s role in cybersecurity, specifically focusing on AI-driven cyber defense and offense mechanisms. It examines the current legal frameworks, highlights gaps, and proposes recommendations for regulating AI technologies in the cybersecurity domain. As artificial intelligence (AI) continues to revolutionize cybersecurity, it introduces both opportunities and legal challenges, particularly in AI-driven cyber defense and offense mechanisms. This article explores the legal implications of AI’s use in cybersecurity, examining the sufficiency of existing frameworks, the ethical concerns in AI-operated cyber attacks, and the accountability issues surrounding AI’s autonomous decisions. By analyzing current laws and identifying key gaps, this research highlights the need for updated legal frameworks to address the rapid advancements in AI-driven cybersecurity.